O30 Pilot evaluation of PrEP EmERGE – a novel digital health innovation designed to support sexual health clinics and HIV-PrEP users. (16th June 2022) - Fitzpatrick, Colin; Richardson, Daniel; Sherriff, Nigel; Whetham, Jennifer
Abstract : Background: 'PrEP-EmERGE' is a co-designed digital health innovation that supports HIV-PrEP users via a novel digital-health pathway and mobile-health application. Method: A cross sectional study using a mixed-methods approach evaluating the usability and acceptability of the PrEP-EmERGE app. Data were collected via an online survey sent to all active users in September-2021. Usability was assessed using a validated usability tool, (SUS). Acceptability was assessed using modified (PREMs). Thematic analysis was used to analyse all free-text responses. Results: 81/133(61%) PrEP EmERGE participants completed an online evaluation. 78/81(96%) identified as cis-male, 74/81 (91%) identified as 'white'. 69/81(85%) reported daily PrEP use, 7/81 (9%) reported using event-based dosing schedule, and 5/81 (6%) were switching between dosing schedules. Overall, the median SUS score was 78/100[IQR=70-92]. There were no differences in median SUS scores by PrEP dosing schedules (p=0.46) or months' of experience of using the app (p=0.38). Overall, 73/81 (90%) would recommend the PrEP EmERGE app to a friend and 78/81 (96%) rated their satisfaction of the app as excellent, good or satisfactory. The free text responses generated three key themes: accessibility (of results); autonomy (taking responsibility for their [sexual] health) and functionality (including technical recommendations for app development and the digital health pathway). Conclusion: Applications such as PrEP EmERGE may provide an important role to help facilitate the increasing number of patients accessing sexual health services for the provision of PrEP. Additionally, the PrEP EmERGE app appears to offer a highly acceptable and usable innovation which may an impact on sustaining PrEP use and optimising adherence.